Adhesion of diabetes personal self-care activities (Research, Society and Development, 2022)
Diabetes is a chronic disease that, as the time of people with the disease increases, can decrease their quality of life. Therefore, the need for health teams to face the development of actions to promote self-care is reinforced. The present study aimed to analyze adherence to self-care activities of people with diabetes treated in the Family Health Strategies. Qualitative and quantitative study, involving 350 people with diabetes treated in 14 Family Health Strategies in a city in the state of Rio Grande do Sul and also 14 professionals from these services. Data collection on people with diabetes occurred through a questionnaire on the profile and the Diabetes Self-Care Activity Questionnaire and that of professionals through interviews. It was identified that most people with diabetes are women, married, retired, have an average of 64.4 years of age and incomplete elementary school. It was found that the item with the highest adherence to self-care by people with diabetes is related to drug therapy and the item with the lowest adherence is related to the dimension of physical activity and glycemic control practices. These data are relevant scientific subsidies for teaching, research, extension, health professionals and health managers, so that they can reflect on the educational and interactive practices developed for the population, with a view to the effectiveness of diabetes treatment, reducing the number complications resulting from the disease and improvement in the quality of life of this population.